Efectuați : a) -100•{3 •[(-3)^100: (-3^99) - (3•3^50) : (-3)^49 ]+1}
Răspunsuri la întrebare
Răspuns de
1
-100•{3 •[(-3)¹⁰⁰: (-3⁹⁹) - (3•3⁵⁰) : (-3)⁴⁹ ]+1}=
-100•{3 •[(-3)¹ - (3⁵¹) : (-3)⁴⁹ ]+1}=
-100•{3 •[(-3)¹ - (3)² ]+1}=
-100•{3•[(-3)-9]+1}=
-100•[3•(-12)+1]=
-100•(-35)=3500
-100•{3 •[(-3)¹ - (3⁵¹) : (-3)⁴⁹ ]+1}=
-100•{3 •[(-3)¹ - (3)² ]+1}=
-100•{3•[(-3)-9]+1}=
-100•[3•(-12)+1]=
-100•(-35)=3500
DanyelaAnaMaria11:
Mulțumesc
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă